Kajian ke atas ciri-ciri optimum dalam penyata kewangan berdasarkan Malaysian accounting standards board (MASB) 1 - Ali Khan, Mohd. Noor Azli; Abdul Rahim, Kamaruzzaman (Faculty of Management and Human Resource Development, 2005)
This study discusses the financial statements presentation practice by listed companies on the Bursa Malaysia. Random sampling technique was used in this study. Out of 598 companies, 281 companies from various industries were selected for the period ended 31st December 2003. An annual report was used to analyse the financial statements presentation practice of the Bursa Malaysia listed companies. This study showed that all the research samples comply with Malaysian Accounting Standards Board (MASB) 1. Furthermore, this study revealed that the rate of English language usage in the annual report is very high (exceed 90%). There are certain different aspects in financial statements presentation which are the arrangement, terms usage and accounting method applied in the financial statements.